Geoinformational analytic control system of the collection of municipal solid waste - Tevyashev, A.; Matviienko, O.; Shiyan, O. (LUBLIN–RZESZOW, 2014)
One of the effective approaches to solve the problem of optimal control of the collection of municipal solid waste in cities and towns on the basis of geoinformational analytic system is studied in the present work. Its structure is shown in the form of three interconnected subsystems: geoinformational system, analytic system, subsystem of nitoring of the refuse collection vehicles. The main attention is focused on the analytic subsystem. The mathematical formulation of the problem of effective planning of the traffic routes of the refuse collection vehicles and efficient algorithm to solve it are set here. The control of implementation of the planned routes is carried out by the subsystem of monitoring of the refuse collection vehicles using GPS-navigation
Keywords: municipal solid wastef; optimization of routes; subsystem of monitoring; energy saving